Renal dysplasia: Part I A clinico-pathological study of 76 cases - Risdon, R. A. (1971)
The clinical and pathological findings in 150 children submitted to partial or total nephrectomy have been reviewed. Histological examination of the kidney removed at operation showed evidence of renal dysplasia in 76 (51%). These 76 patients were divided into three main groups on the basis of the pathological changes found in the kidney and the associated urinary tract anomalies. In group 1, gross cystic renal dysplasia was associated with absence or atresia of the renal pelvis and ureter. In group 2, renal dysplasia was segmental; the ureter, although patent, had some anatomical or functional abnormality which resulted in urinary stasis or reflux. In many of these patients dysplasia was confined to the upper pole of a `duplex' kidney which was drained by an ectopic ureterocele. In group 3, renal dysplasia was associated with obstruction of the lower urinary tract, most commonly by posterior urethral valves. In group 1 dysplasia was total, involving the whole kidney, whilst in groups 2 and 3 dysplasia tended to be segmental; in the majority some normal renal tissue was present. Pyelonephritis was a very common complication, but was present only in patients from groups 2 and 3, in whom a lumen was present in the draining ureter, and not in patients from group 1 in whom the ureter was atretic or absent, and the kidney not functioning. It appears that urinary obstruction, stasis, or reflux are the principal factors predisposing to and promoting pyelonephritis in dysplastic kidneys. There seems to be no reason to suppose that dysplastic renal tissue is abnormally susceptible to infection since pyelonephritic changes were lacking in those cases in which dysplasia was most severe.